Askeri darbelerin Suriye siyasetine etkileri (1949-1970) - Demirel, Doğan (My University, 2019)
unknown
Keywords: Askeri Darbeler; Ba'ath Party; Baas Partisi; Coups d’état; Darbeler; Hafız Esad Military Coups; Hafiz Asad; Middle East; Orta Doğu; Suriye; Suriye Siyaseti; Syria; The Politic of Syria